Makanan Awetan Ikan Leiognathus equulus Asal Bangka Belitung melalui Fermentasi Bakteri Asam Laktat dan Uji Organoleptiknya - Yovita Harmiatun; Adisti Ratnapuri; Winona Elita (Jurnal Pro-Life, 2022)
This study used Leiognathus equulus (fish pepetek) with simple biotechnology through lactic acid fermentation to produce preserved food that has intact fish texture, fragrant aroma, and delicious taste. The data collection technique used a closed questionnaire to the respondents. The data obtained were analyzed using descriptive analysis of percentages and table tabulation of the percentage of preference criteria. The results showed that the preserved food products that were most liked by the public, namely the first sample fermentation was fermentation in the B3 sample, namely with a concentration of 30 grams of granulated sugar, 2 grams of Lactobacillus bulgaricus bacteria and 10 grams of salt. Percentage of assessment of the appearance of 94%, which is highly preferred with very attractive appearance indicators, fish shape that is intact, soft and fresh brownish white color. The organoleptic assessment of taste, which is 86%, is very favorable with indicators that it tastes very good, sweet and savory. The aroma is 90%, it is highly preferred with the indicator that the aroma is very delicious, fresh and smells like fruit. The organoleptic assessment of texture is 92% which is very favorable with indicators of soft, intact texture and softer bones fresh and fragrant like fruit. The organoleptic assessment of texture is 92% which is very favorable with indicators of soft, intact texture and softer bones.